2003
DOI: 10.1074/jbc.c300047200
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Elongin A Is Not Essential for Cell Viability but Is Required for Proper Cell Cycle Progression with Limited Alteration of Gene Expression

Abstract: (pol II) 1 is regulated by the concerted action of a set of general transcription factors that control the activity of pol II during the initiation and elongation stages of transcription. At least six general transcription initiation factors (TFIIA, TFIIB, TFIID, TFIIE, TFIIF, and TFIIH) have been identified in eukaryotic cells and found to promote the selective binding of pol II to promoters and to support a basal level of transcription (1). In addition to the general initiation factors, at least 17 elongatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Previous studies suggested that Elongin A is not generally required for transcription in vivo (19,28). Supporting this idea, shRNA-mediated depletion of Elongin A or deletion of the Elongin A gene neither altered the distribution of RNAPII in cell nuclei nor impaired production of the majority of nascent RNA (Fig.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Previous studies suggested that Elongin A is not generally required for transcription in vivo (19,28). Supporting this idea, shRNA-mediated depletion of Elongin A or deletion of the Elongin A gene neither altered the distribution of RNAPII in cell nuclei nor impaired production of the majority of nascent RNA (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…We previously carried out a comprehensive microarray analysis that revealed that expression of only a small fraction of genes (铣3-4%) is affected in Elongin A-deficient mouse ES cells, raising the possibility that Elongin A is not a global regulator of gene expression but rather controls the expression of select genes (28). More recently, we have generated Elongin A-deficient mice (29) and showed that Elongin A plays a crucial role in expression of a variety of genes for neural development (19).…”
mentioning
confidence: 99%
“…Previously, we demonstrated that one of the proteins in this class, dELL, is essential in Drosophila and is not functionally redundant with other members (10). A recent report by Yamazaki et al indicates that mammalian elongin A is not essential for viability of mouse ES cells but is important for proper cell cycle progression and expression of a specific subset of genes (43). Whether elongin A is required for normal mouse development is not known.…”
Section: Discussionmentioning
confidence: 99%
“…17 Exons 8-10 of the Elongin A gene were replaced with a neomycin cassette in the gene-targeting vector (Figure 1a). 18 The mutant ES cell clones with a disrupted Elongin A locus were used to obtain the germline chimeras that, in turn, were used to generate the heterozygous F1 mutant mice. The genotypes were determined using the polymerase chain reaction (PCR), and the loss of Elongin A expression was confirmed by reverse transcriptase (RT)-PCR (Figure 1b and c).…”
Section: Resultsmentioning
confidence: 99%
“…Elongin A mutant ES cell clones were generated as described previously 18 and microinjected into blastocysts for the generation of chimeric mice. Chimeric males were crossed with C57BL/6 females, and agouti-colored offspring were analyzed for the germline transmission of the Elongin A mutation.…”
Section: Methodsmentioning
confidence: 99%